2012
DOI: 10.1515/bmc.2011.049
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells for cardiac regeneration and possible roles of the transforming growth factor-β superfamily

Abstract: Heart failure is a leading cause of death worldwide. Studies of stem cell biology are essential for developing efficient treatments. Recently, we established and characterized c-kit-positive cardiac stem cells from the adult rat heart. Using a MethoCult culture system with a methyl-cellulose-based medium, stem-like left-atrium-derived pluripotent cells could be regulated to differentiate into skeletal/cardiac myocytes or adipocytes with almost 100% purity. Microarray and pathway analyses of these cells showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Makkar et al reported that cardiosphere-derived cells were used for phase 1 clinical trials, and they warrant a phase 2 study [42]. Readers can refer to review articles for details about other types of cardiac stem cells [21, 22, 4348]. …”
Section: Isolation Of Cardiac Stem Cells From the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Makkar et al reported that cardiosphere-derived cells were used for phase 1 clinical trials, and they warrant a phase 2 study [42]. Readers can refer to review articles for details about other types of cardiac stem cells [21, 22, 4348]. …”
Section: Isolation Of Cardiac Stem Cells From the Heartmentioning
confidence: 99%
“…In human biopsies, 80% of cardiosphere-derived stem cells from the myocardial infarcted patients were c-kit and MDR-1 double positive [64]. The role of c-kit may change according to its expression level [22]. …”
Section: Characteristics Of Immunopurified C-kitpos Cardiac Stem Cmentioning
confidence: 99%
“…Furthermore, the addition of noggin resulted in the downregulation of adipogenesis and produced high yields of beating cardiomyocytes. Further discussion regarding the results of this report has been described elsewhere [50, 51]. Dissection of the in vivo function of noggin and/or TGF- β is an ongoing area of research.…”
Section: Microarray Analysis Comparing Undifferentiated and Differmentioning
confidence: 99%
“…iPS cells derived from patients or iPS cells engineered with a disease gene are differentiated into myocytes and are now being used to model diseases in vitro [52]. At present, only channelopathies, such as LQTS-type 2 [53] and LQTS-type 3 [54], have been well studied because of the comparatively easy functional analysis needed for characterization [51]. However, more complicated diseases will require culture methods that more closely model the native tissue environment.…”
Section: Modeling Diseases In Vitro Using 3d Culturesmentioning
confidence: 99%
“…The results suggested that these CSCs retained multiple developmental potential to some extent. Consequently, we investigated these CSCs in detail, hoping to establish the regeneration method by using c-Kit-positive cardiac cells [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%